2016
DOI: 10.3389/fneur.2016.00180
|View full text |Cite
|
Sign up to set email alerts
|

A “Wear and Tear” Hypothesis to Explain Sudden Infant Death Syndrome

Abstract: Sudden infant death syndrome (SIDS) is the leading cause of death among USA infants under 1 year of age accounting for ~2,700 deaths per year. Although formally SIDS dates back at least 2,000 years and was even mentioned in the Hebrew Bible (Kings 3:19), its etiology remains unexplained prompting the CDC to initiate a sudden unexpected infant death case registry in 2010. Due to their total dependence, the ability of the infant to allostatically regulate stressors and stress responses shaped by genetic and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 159 publications
4
29
0
Order By: Relevance
“…Cohort studies are also problematic due to the difficulty of finding suitable controls and accounting for external stressors, which vary widely among countries, cultures, and socio-economic status and can render association studies ambiguous. These methodological difficulties have resulted in over 100 explanations for SIDS that appeared in Medical Hypotheses [5] and much confusion between cause and effect. For instance, it has been reported that breastfeeding for a duration of at least two months is associated with a reduced risk of SIDS [51], however, it does not mean that breastfeeding confers protection against SIDS, as an infant's refusal to feed may be a symptom of other SIDS risk factors, like MNC [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cohort studies are also problematic due to the difficulty of finding suitable controls and accounting for external stressors, which vary widely among countries, cultures, and socio-economic status and can render association studies ambiguous. These methodological difficulties have resulted in over 100 explanations for SIDS that appeared in Medical Hypotheses [5] and much confusion between cause and effect. For instance, it has been reported that breastfeeding for a duration of at least two months is associated with a reduced risk of SIDS [51], however, it does not mean that breastfeeding confers protection against SIDS, as an infant's refusal to feed may be a symptom of other SIDS risk factors, like MNC [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The allostatic load hypothesis, initially proposed to explain how stress influences the pathogenesis of diseases [56] and later applied to specific disorders [e.g., 57], proposes that prolonged and repetitive stressful, painful, and traumatic experiences during the periand pre-natal developmental periods lead to the accumulation of allostatic load that may be lethal [5]. Thereby, both hypotheses consider external stressors but disagree on the definition of at-risk infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations